Cinema e sociabilidade nas cidades do café: Franca e Ribeirão Preto (1890 1930) - Azevedo, Veruschka de Sales (2016)
This work aims to record the arrival of silent cinema in the coffee towns, Franca and Ribeirão Preto, in the late nineteenth century and the first two decades of the twentieth century, seeking to understand how cinema influenced the sociability spaces of those cities that began to urbanize and experience the arrival of a set of icons of modernity, and the film of them. The historical period (1890-1930) corresponds to the economic and political rise of the Paulista coffee elite in the First Republic. This reference therefore puts the coffee cities at the center of urban transformations within a period we call Belle Èpoque hick, when the speech of civilization and progress was used in city leading. The analysis of documents on cinema in those early times in the cities of Franca and Ribeirão Preto, showed us a rich and diverse world of entertainment, marked by the theater, performances of "vaudeville", the opera, the circus, and most exciting of all the entertainment, cinema. In this sense, the records in the press of the period, daily and even in advertisements and some city cinemas bankruptcy documents point to an intense cultural life that led some area resident to trade the production and exhibition of cinema. These documents are important because they show up how was the reception of the film, the relationship between the coffee economy and the world of entertainment, leading us to the interesting record of the silent cinema history in the coffee grounds